Distal airway function in symptomatic subjects with normal spirometry following World Trade Center dust exposure - Oppenheimer, Beno W; Goldring, Roberta M; Herberg, Matthew E; Hofer, Ira S; Reyfman, Paul A; Liautaud, Sybille; Rom, William N; Reibman, Joan; Berger, Kenneth I (Chest, 2007)
Following collapse of the World Trade Center (WTC), individuals reported new-onset respiratory symptoms. Despite symptoms, spirometry often revealed normal airway function. However, bronchial wall thickening and air trapping were seen radiographically in some subjects. We hypothesized that symptomatic individuals following exposure to WTC dust may have functional abnormalities in distal airways not detectable with routine spirometry. One hundred seventy-four subjects with respiratory symptoms and normal spirometry results were evaluated. Impedance oscillometry (IOS) was performed to determine resistance at 5 Hz, 5 to 20 Hz, and reactance area. Forty-three subjects were also tested for frequency dependence of compliance (FDC). Testing was repeated after bronchodilation. Predominant symptoms included cough (67%) and dyspnea (65%). Despite normal spirometry results, mean resistance at 5 Hz, 5 to 20 Hz, and reactance area were elevated (4.36 +/- 0.12 cm H(2)O/L/s, 0.86 +/- 0.05 cm H(2)O/L/s, and 6.12 +/- 0.50 cm H(2)O/L, respectively) [mean +/- SE]. Resistance and reactance normalized after bronchodilation. FDC was present in 37 of 43 individuals with improvement after bronchodilation. Symptomatic individuals with presumed WTC dust/fume exposure and normal spirometry results displayed airway dysfunction based on the following: (1) elevated airway resistance and frequency dependence of resistance determined by IOS; (2) heterogeneity of distal airway function demonstrated by elevated reactance area on oscillometry and FDC; and (3) reversibility of these functional abnormalities to or toward normal following administration of a bronchodilator. Since spirometry results were normal in all subjects, these abnormalities likely reflect dysfunction in airways more distal to those evaluated by spirometry. Examination of distal airway function when spirometry results are normal may be important in the evaluation of subjects exposed to occupational and environmental hazards.